UPPER MANTLE CONVECTION RELATED TO SUBDUCTION ZONE AND APPLICATION OF THE MODEL TO INVESTIGATE THE CRETACEOUS-CENOZOIC GEODYNAMICS OF CENTRAL EAST ASIA AND THE ARCTIC - L. I. Lobkovsky; M. M. Ramazanov; V. D. Kotelkin (Геодинамика и тектонофизика)
A geodynamic model of upper mantle convection related to the Pacific subduction zone is mathematically substantiated and applied to investigate the Cretaceous-Cenozoic evolution of Central East Asia (CEA) and the Arctic. We present a solution for the two-dimensional stationary problem of thermal convection in the upper mantle layer, considering different Rayleigh numbers and taking into account the influence of the subduction process and lithospheric movements along the upper mantle base. We describe the results of 3D modeling of nonstationary upper mantle convection in a subduction zone. Our data give grounds to propose explanations for the entire spectrum of tectonic-magmatic processes developing within CEA in the Cenozoic and the Arctic in the Upper Cretaceous and Cenozoic. We discuss the reasons why the lithosphere in CEA and the Arctic is generally shifting towards the Pacific subduction zone, considering the presence of separate magmatic provinces and rift zones. In our opinion, this is due to the existence of a large horizontally elongated convective cell, which interior is composed of smaller isometric cells. This long cell creates the effect of conveyor dragging of the lithosphere, while its internal cells produce the effect of upper mantle plumes.